Shape control of zincblende CdSe nanoplatelets. Issue 80 (19th September 2016) - Bertrand, Guillaume H. V.; Polovitsyn, Anatolii; Christodoulou, Sotirios; Khan, Ali Hossain; Moreels, Iwan
Abstract : Water matters: the aspect ratio of CdSe nanoplatelets can be precisely tuned by adjusting the fraction of hydrated cadmium acetate in the synthesis. Abstract : The lateral dimensions of CdSe nanoplatelets have a strong and unique influence on their opto-electronic properties, with sizes that can be tuned from the weak to the strong exciton confinement regime. There are state-of-the-art reports on several nanoplatelet syntheses; however, at present only the thickness is well-controlled. We demonstrate here that we can achieve a control over the aspect ratio and overall nanoplate area by carefully adjusting the reagents that induce the in-plane growth. A variation of the fraction of hydrated Cd(OAc)2 in a Cd(OAc)2 /Cd(OAc)2 ·2H2 O mixture tailors the nanoplatelet aspect ratio. This occurs independently of the reaction time, which can be used to fine-tune the overall length and width. An interpretation is given by the in situ formation of a small amount of hydroxide anions that alter the surface energy of specific planes.